2018
DOI: 10.1186/s12954-018-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization among street-involved youth who use illicit drugs in Vancouver, Canada: a longitudinal analysis

Abstract: BackgroundStreet-involved youth who use illicit drugs are at high risk for health-related harms; however, the profile of youth at greatest risk of hospitalization has not been well described. We sought to characterize hospitalization among street-involved youth who use illicit drugs and identify the most frequent medical reasons for hospitalization among this population.MethodsFrom January 2005 to May 2016, data were collected from the At-Risk Youth Study (ARYS), a prospective cohort study of street-involved y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…The relationship between homelessness and mental illness is bi-directional; homelessness can directly undermine mental health, and mental illness can directly lead to becoming homeless [30]. Homeless populations have high rates of mental illness, with studies finding between 42–80% of people who are homeless experience mental health struggles [24,31,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between homelessness and mental illness is bi-directional; homelessness can directly undermine mental health, and mental illness can directly lead to becoming homeless [30]. Homeless populations have high rates of mental illness, with studies finding between 42–80% of people who are homeless experience mental health struggles [24,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Despite homeless people’s many vulnerabilities to poor health—such as injuries, harsh weather exposure, and assault —there are numerous barriers to care—such as cost, lack of transport, and fear of judgement [30]. This suggests homeless people can be reluctant to use health services and delay seeking help until their conditions deteriorate, increasing the risk of hospitalisation [30]. Despite this, there is limited information on the experiences of those who identify as LGBTIQ+.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…soft‐tissue infections, psychiatric illness, pneumonia, cardiovascular complications, overdose) that often result in increased hospital service utilisation [1–2]. A study involving 1216 street‐involved youth who use drugs found that 373 (30.7%) participants were admitted to hospital in the previous 6 months at some point between January 2005 and May 2016, with mental illness being the top reported reason for admission (37.8%) [3]. Notably, in recent years, there has been a striking increase in hospital admissions for infective endocarditis, a potentially fatal consequence of injection drug use [4].…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding services for these health issues often allows them to deteriorate until they require hospitalization, which increases the health and economic burden associated with treating these conditions [35,37,39,40]. Previous studies of street-involved youth have found that nearly one-third report being hospitalized in the last 6 months and many authors have raised concerns about how cannabis use affects the acute and long-term health of vulnerable populations such as economically disadvantaged youth [41,42].…”
mentioning
confidence: 99%